2016
DOI: 10.1073/pnas.1513302113
|View full text |Cite
|
Sign up to set email alerts
|

A transcriptional signature of hub connectivity in the mouse connectome

Abstract: Connectivity is not distributed evenly throughout the brain. Instead, it is concentrated on a small number of highly connected neural elements that act as network hubs. Across different species and measurement scales, these hubs show dense interconnectivity, forming a core or "rich club" that integrates information across anatomically distributed neural systems. Here, we show that projections between connectivity hubs of the mouse brain are both central (i.e., they play an important role in neural communicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
318
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(353 citation statements)
references
References 51 publications
33
318
2
Order By: Relevance
“…Global network properties have been found to mirror patterns in gene expression (Fulcher and Fornito, 2016, Rubinov et al., 2015, Vértes et al., 2016), and more specifically, the association between MAPT expression and connection strength reflects the importance of the tau protein in maintaining axonal integrity by stabilizing microtubules (Lindwall and Cole, 1984). In humans, previous imaging studies have linked single gene variants with patterns of change in brain imaging (Filippini et al., 2009, Mata et al., 2014, Whitwell et al., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Global network properties have been found to mirror patterns in gene expression (Fulcher and Fornito, 2016, Rubinov et al., 2015, Vértes et al., 2016), and more specifically, the association between MAPT expression and connection strength reflects the importance of the tau protein in maintaining axonal integrity by stabilizing microtubules (Lindwall and Cole, 1984). In humans, previous imaging studies have linked single gene variants with patterns of change in brain imaging (Filippini et al., 2009, Mata et al., 2014, Whitwell et al., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptional profiles also exhibit relationships with the topological roles of brain areas in the macroscale connectome. In the mouse brain, highly connected and highly central areas exhibit a common and distinct topological profile, specifically involving genes regulating oxidative metabolism, suggestive of links between network topology and metabolic demand 128 . A separate study found evidence of elevated expression of genes associated with cognition, learning and memory in hub nodes of the mouse brain 129 .…”
Section: Current Frontiersmentioning
confidence: 99%
“…26) but not previously related to measures of cortical shrinkage or myelination. Recently, several studies have linked brain regional gene expression to axonal connectivity in the mouse (27,28) and functional MRI networks in humans (29,30), but there have been no previous efforts to investigate genetic mechanisms of adolescent myelination of human cortex.…”
Section: Significancementioning
confidence: 99%